Novels of S. Nadolny as Part of German Road Narrative Works at the End of 20th Century - Aydarova, Alsou M.; Strakhova, Irina V.; Mazaeva, Tatjana V. (Journal of History Culture and Art Research, 2017)
The article considers the background of the genre definition issue of the novel in general, and the nontraditional novel genre “road narrative” in particular. The article also highlights the essential features of this non-canonical literary genre as well as manifestation peculiarities of this phenomenon in German national literature. The authors attempt to define to what extent the creativity of the contemporary German writer Sten Nadolny (namely his novels Travelcard” (Netzkarte, 1981) and “He or me” (Eroderich, 1999)) has the capacity to reflect the specific character in terms of development of the given genre. Comprehensive analysis enabled the authors to arrive at the conclusion that the novels of Nadolny under consideration are the icon of road narrative genre in German literature. Using the culture-historical, comparative-typological and biographical methods it was inferred that the works of Nadolny illustrate the specific features of transformation of this literary genre during the 70s-90s of the 20th century.